2014
DOI: 10.1364/ol.39.003794
|View full text |Cite
|
Sign up to set email alerts
|

400  mW external cavity diode laser with narrowband emission at 445  nm

Abstract: A high-power external cavity diode laser (ECDL) system with narrowband emission is presented. The system is based on a commercially available high-power GaN laser diode. For the ECDL, a maximum optical output power of 400 mW in continuous-wave operation with narrowband emission is achieved. Longitudinal mode selection is realized by using a surface diffraction grating in Littrow configuration. A spectral width of 20 pm at 445 nm with a side-mode suppression ratio larger than 40 dB is achieved. This concept ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The deviation in the conversion coefficient by a factor of 3.6 as well as the larger beam waist radius in our experiment is probably due to the nondiffraction limited fundamental beam of the ECDL. As reported in [13], the second moment beam propagation factors for the ECDL emission at 400 mW are M 2 lat:;4σ 8.2 and M 2 vert:;4σ 4.9 in the lateral and vertical direction, respectively. Figure 3 also shows an increasing deviation of the experimental data points from the numerical fit for higher pump powers.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…The deviation in the conversion coefficient by a factor of 3.6 as well as the larger beam waist radius in our experiment is probably due to the nondiffraction limited fundamental beam of the ECDL. As reported in [13], the second moment beam propagation factors for the ECDL emission at 400 mW are M 2 lat:;4σ 8.2 and M 2 vert:;4σ 4.9 in the lateral and vertical direction, respectively. Figure 3 also shows an increasing deviation of the experimental data points from the numerical fit for higher pump powers.…”
supporting
confidence: 58%
“…However, their broad spectral emission limits their applicability for frequency conversion. In order to reduce the spectral width, a high-power GaN laser diode in an external cavity diode laser (ECDL) system in Littrow configuration was recently presented by the authors [13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Another 405 nm external-cavity diode laser was demonstrated by Lv et al in 2013, with an output power of the laser around 1 mW and with a tuning range around 4.5 nm [12]. Recently, Ruhnke et al reported an external-cavity diode laser at 445 nm, where a maximum output power of 400 mW was obtained, and the tuning range was around 3 nm [13]. This externalcavity diode laser system was used as a pump source to generate deep violet radiation at 222.5 nm [5].…”
Section: Introductionmentioning
confidence: 99%